CLINICAL EFFICACY OF UDVARTANA WITH LEKHANA BASTI IN HYPERCHOLESTEROLEMIA - S J, *Lolashri; M Goud, Kiran; R, Usha (International Journal of Ayurveda and Pharma Research, 2019)
Now a day, due to increase in industrialized population include a sedentary lifestyle and a diet characterized by the excessive consumption of saturated fats, trans fatty acids and cholesterol which tends to increase blood cholesterol levels. Raised total cholesterol is a major cause of disease burden in both the developed and developing world as a risk factor for Ischemic heart disease and stroke. In Ayurveda, this condition can be considered under Santarpanotthavyadhi.  Due to Santarpanothanidanas there will be increase in the Pichilla and Snehagunas which in turn causes Ama, if further same nidanas are continued leads to Madhuratara of Ama and Annarasa causes the circulation of increased Medaie: Shareera Anukraman Atisnehan Medo Janayati.  To combat this condition Acharyas have mentioned about VatagnaAnnapana, Ruksha- Ushna i.e., Ruksha Udvartana, Lekhana Basti etc lines of treatment.  Hence this study was taken up to see the efficacy of the treatment protocol mentioned for the better management.It was an open label clinical study done on 10 patients.  Patients were subjected to Sarvanga Udvartana with Kolakulatthadichurna and Lekhanabasti for a period of fifteen days.In the present study, the effect of the treatment has shown statistically Highly Significant   (p<0.01) results on Serum Cholesterol and LDL. As the study was conducted to know the combined effect of Bahyaupakrama along with the Lekhanabasti, the usefulness of individual Upakrama found limited.  So probably administration of these upakramas in single dimension one after the other along with proper diet and physical exercise in frequent intervals may yield good results.